Analysis Of Treatment Of Leaf Steel As A Cutting Knife With Quenching Method To Increase Hardness - M. Ganu Hersandi; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2022)
Heat treatment carried out on steel materials will have an effect on the hardness and changes in metal structure in iron or steel. The addition of this hardness depends on the type of steel material used, temperature, and the cooling medium used such as oil, air, and water. In this study, the hardness of the iron cutting knife was increased through a heat treatment process to determine the effect of the hardness of the cutting knife on the result of cutting a 2 mm iron plate. The test object is a cutting knife which will be heated to a temperature of 850Â°C, cooled using SAE 35 oil. The test results show that the harder the cutting knife, the smaller the angle of inclination of the 2 mm plate..